Phenomenological Study on Diamond Jewelry Purchase Decisions as a Tertiary Need (A Study on the FebriMela Brand) - Pebri Melati; Amie Kusumawardhani (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research seeks to explore the decision-making process behind purchasing diamond jewelry as a way of fulfilling tertiary needs, with a specific focus on the local brand FebriMela. The motivation to buy diamond jewelry extends beyond functional purposes, encompassing emotional, psychological, and social dimensions such as boosting self-confidence, gaining social acknowledgment, and shaping personal identity. Employing a qualitative approach through a phenomenological lens, the study investigates consumers' subjective experiences. Data were gathered through in-depth interviews, observations, and documentation involving individuals who have bought FebriMela jewelry. The findings reveal that brand trust plays a central role in purchase decisions, followed by emotional experiences and social interactions with the sellers. These results highlight the significance of emotional value in the consumption of luxury goods in Indonesia and offer fresh perspectives on local consumer behavior regarding diamond jewelry. This study aims to contribute to the broader understanding of luxury consumer behavior, particularly within the Indonesian cultural context.